2021
DOI: 10.1111/cmi.13322
|View full text |Cite
|
Sign up to set email alerts
|

NS1 ‐mediated upregulation of ZDHHC22 acyltransferase in influenza a virus infected cells

Abstract: Influenza A viruses contain two S-acylated proteins, the ion channel M2 and the glycoprotein hemagglutinin (HA). Acylation of the latter is essential for virus replication.Here we analysed the expression of each of the 23 members of the family of ZDHHC acyltransferases in human airway cells, the site of virus replication. RT-PCR revealed that every ZDHHC acyltransferase (except ZDHHC19) is expressed in A549 and Calu cells. Interestingly, expression of one ZDHHC, ZDHHC22, is upregulated in virusinfected cells; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Recently, a genome-wide screen using CRISPR/Cas9 was conducted to identify host factors that may potentially participate in the replication of certain viruses, such as SARS-CoV-2 ( 90 ), HIV ( 91 ), arthritic alphaviruses ( 92 ), Coxsackie virus ( 93 ), Venezuelan equine encephalitis virus (VEEV) ( 94 ) and influenza virus ( 95 ). For the influenza virus, it was demonstrated that inactivation of specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7 and ZDHHC22, can induce protection against cell death during infection ( 96 100 ). Because of the high throughput and precise editing features of the CRISPR/Cas9 screening system, one can quickly and accurately identify specific genes and proteins involved in the pathogenesis of viruses.…”
Section: Crispr-cas9 Applicationsmentioning
confidence: 99%
“…Recently, a genome-wide screen using CRISPR/Cas9 was conducted to identify host factors that may potentially participate in the replication of certain viruses, such as SARS-CoV-2 ( 90 ), HIV ( 91 ), arthritic alphaviruses ( 92 ), Coxsackie virus ( 93 ), Venezuelan equine encephalitis virus (VEEV) ( 94 ) and influenza virus ( 95 ). For the influenza virus, it was demonstrated that inactivation of specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7 and ZDHHC22, can induce protection against cell death during infection ( 96 100 ). Because of the high throughput and precise editing features of the CRISPR/Cas9 screening system, one can quickly and accurately identify specific genes and proteins involved in the pathogenesis of viruses.…”
Section: Crispr-cas9 Applicationsmentioning
confidence: 99%
“…Recently, genome-wide CRISPR/Cas9 screening has been used to identify host factors that are potentially involved in the replications of some viruses, such as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 96 ], HIV [ 97 ], arthritogenic alphaviruses [ 98 ], Coxsackievirus [ 99 ], Venezuelan equine encephalitis virus (VEEV) [ 100 ], and influenza virus [ 101 ]. For the influenza virus, it has been demonstrated that inactivation of the specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7, and ZDHHC22, can induce protection against cell death by influenza virus infection [ 102 , 103 , 104 , 105 , 106 ]. With the advantages of having a high throughput and allowing the precise editing of the CRISPR/Cas9 screening system, we can quickly and accurately identify the specific genes and proteins contributing to the pathogenesis of various viruses.…”
Section: Crispr/cas System In Virology Researchmentioning
confidence: 99%
“…In summary, all DHHCs required for acylation of HA and M2 (2, 8, 15 and 20) and S and E (8,9,20) in human cells are present in the genome of the reservoir hosts of Flu A and CoVs. Likewise, the gene of DHHC22 which is upregulated during an influenza virus [87] infection is also encoded in all hosts of Flu A. Interestingly, all the virus' hosts lack a comparable set of DHHCs. All animals that have fewer DHHC genes than humans, lack the gene for DHHC11.…”
Section: Number and Type Of Dhhc Genes In Animal Hosts Of Influenza A...mentioning
confidence: 99%